THE USE MIND MAP TO IMPROVE STUDENTS - Pathul Indirana; Lalu Isnaeni Rahman (PIKTORIAL : Journal of Humanities, 2019)
The aim of the study is to improve the students’ skill in learning English especially writing descriptive text. This research belongs to experimental research. Based on the observations, the problems found in teaching writing were ineffective strategy and instruction, language structure, vocabulary and lack of motivation. The data were obtained by interviewing the tenth grade students of SMK Yusuf Abdussatar Kediri Lombok Barat, holding the discussion with the English teacher, and doing observations in the English teaching and learning process. The instruments of the study were a pre-test and post-test, observation guidelines, and interview guidelines. Qualitative and quantitative methods were used to collect the data. The data were analyzed from the field notes, interview transcript and the result of the pre-test and post-test. The result of the study showed that the students’ writing descriptive text in English teaching and learning process improved through mind map. The result of the research showed that the mean score of post-test was higher than that of the mean score of the pre-test. The mean score of pre-test was (62.78) and the mean score of post-test was (75. 89). Thus, there was an increasing point of 13. 11. Keywords: mind-map, writing, descriptive text.